One decade of b-value variations from volcano-tectonic seismicity as an early indicator of episodes of crisis in a volcano: the case of Copahue, Southern Andes - Farías, Cristian; Lazo, Jonathan; Basualto , Daniel; Saavedra, Marcela; Muñoz-Quiroz, Felipe; Zúñiga-Urrea, Lucas; Martínez-Bravo, Rodrigo; Huentenao-Inostroza, Ian; Sáez-Opazo, Ramón (Frontiers in Earth Science, 2023)
Volcanoes can enter in episodes of unrest, which might end later in an eruption, with little warning.They are normally produced due to the inner dynamics of the volcano, but can also be triggered by external earthquakes. To detect these periods early, it becomes crucial to understand the dynamics of the different structures (such as fault systems) of the volcano, as they can act as magma pathways and can also generate instabilities on it. In this article we study the seismicity of Copahue (central-south Chile), which sits atop a complex system of faults, and was importantly affected by the 2010 Mw 8.8 Maule earthquake. We focused ourselves in the temporal variations of the b-value of the Gutenberg-Richter law during the 2012-2022 period. During this timeframe the volcano had a series of crises, which led to seven eruptive phases. Our results show that the system does exhibit signs of a future unrest phase weeks to months before there is a change on its alert level, and they are mostly linked to the activity of a N-S fault zone, located not beneath the main crater of Copahue, but around 10 km to the East. Most of the crises start after drops in the b-value of this structure, with sudden variations in b-value being also noticeable as a response to the 2015 Mw 8.3 Illapel earthquake. Our results show a correlation between instances of fluid injection and release in the relevant structures of an active volcano with the variations of the b-value. This allow us to use the temporal variations of the b-value as a tool to anticipate the inner dynamics of the system, particularly when there is a strong structural control on it, such as in the case of Copahue. We also found out that the influence of the 2010 Mw 8.8 Maule earthquake was long-lived, affecting mostly the structures that later destabilized the volcano for the most part of a decade, therefore enhancing magma injection into the whole system. This seems to have changed since 2021, which might indicate a waning in the influence of the megathrust earthquake in Copahue volcano.